Structure optimization and electronic modulation of sulfur-incorporated cobalt nanocages for enhanced oxygen evolution. (13th August 2021) - Fan, Ruo-Yao; Xie, Jing-Yi; Ma, Yu; Fu, Jia-Yu; Liu, Hai-Jun; Li, Meng-Xuan; Yu, Wen-Li; Liu, Da-Peng; Chai, Yong-Ming; Dong, Bin
Abstract: Cobalt-based oxides and hydroxides have always been one of the optimal catalysts for Oxygen Evolution Reaction (OER) in alkaline environment in recent years. However, it remains a challenge for simple cobalt oxides such as CoO, Co3 O4 and CoOOH to provide high catalytic activity both with ideal conductivity and stability. Herein, we prepared a new type of sulfur-incorporated cobalt oxide nanocages as high efficiency OER catalyst using Co-MOF as precursor. With the help of sodium sulfide, one step water-warm immersion-alcohol refluxing method can achieve the cavitation of precursors and uniform incorporation of sulfur atoms meanwhile. The hollow cubic structure constructed by fluffy nanosheets is beneficial to the exposure of active sites, the regulation of electronic structure and improve the electron transfer speed. After electrochemical testing, the prepared CoS@CoO showed outstanding OER activity compared with other cobalt-based catalysts. More importantly, this material has also withstood the electrochemical test of long range due to the stable structural foundation provided by Co-MOF. This work comes up with a new idea for OER activity promotion of hollow doped cobalt-based catalysts through morphology control and electronic structure optimization. Graphical abstract: Image 1 Highlights: Sulfur-incorporated cobalt oxide nanocages provide the large surface area and fast electron transfer. The one-step refluxing can realize the stable structure with uniform incorporation of S atoms. Co-MOF as precursor can provide the hollow cubic with more exposed sites for OER. CoS@CoO showed outstanding OER activity compared with other cobalt-based oxides.